2015
DOI: 10.1049/iet-its.2014.0053
|View full text |Cite
|
Sign up to set email alerts
|

Determinants of driver response to variable message sign information in Athens

Abstract: Variable message signs -which comprise a type of advanced traveller information systems -can affect driver behaviour, especially considering route choice. Hence, their operation is integrated in traffic management strategies for the mitigation of traffic congestion. This research explores the factors determining driver response to variable message signs (VMSs) in the city of Athens. A stated preference questionnaire survey is undertaken and discrete choice analysis is performed towards this aim. More specifica… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
17
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 15 publications
(20 citation statements)
references
References 53 publications
1
17
2
Order By: Relevance
“…(Wardman et al, 1997;Al-Deek et al, 2012). Delays attribute to accidents have the larger impacts on route choice than other stated causes, such as roadworks and congestion (Wardman et al, 1997;Chatterjee et al, 2002;Spyropoulou and Antoniou, 2014;Sharples et al, 2016). Jindahra and Choocharukul (2013) employed the mixed logit model to analyze drivers' preference for VMS contents, the results showed that drivers would like to receive the suggested route diversion information, qualitative delay information and road construction information when they are at congested conditions.…”
Section: Subjective Measure For Vms Contents and Formatsmentioning
confidence: 99%
See 1 more Smart Citation
“…(Wardman et al, 1997;Al-Deek et al, 2012). Delays attribute to accidents have the larger impacts on route choice than other stated causes, such as roadworks and congestion (Wardman et al, 1997;Chatterjee et al, 2002;Spyropoulou and Antoniou, 2014;Sharples et al, 2016). Jindahra and Choocharukul (2013) employed the mixed logit model to analyze drivers' preference for VMS contents, the results showed that drivers would like to receive the suggested route diversion information, qualitative delay information and road construction information when they are at congested conditions.…”
Section: Subjective Measure For Vms Contents and Formatsmentioning
confidence: 99%
“…This includes: (i) revealed preference (RP) questionnaire surveys (Chatterjee et al, 2002;Kilpeläinen and Summala. 2007;Wang et al, 2009;Hassan and Abdel-Aty, 2011), stated preference (SP) questionnaire survey (Benson, 1996;Emmerink et al, 1996;Wardman et al, 1997;Al-Madani andAl-Janahi, 2002a, 2002b;Hassan and Abdel-Aty, 2011;Gan and Ye, 2011;Jindahra and Choocharukul, 2013;Spyropoulou and Antoniou, 2014;Ronchi et al, 2016) and a combination of SP and RP survey (Al-Deek et al, 2012), (ii) driving simulators (Mahmassani and Chen, 1991;Wang and Cao, 2005;Lai, 2008Lai, , 2012Shinar and Vogelzang, 2013;Williams et al, 2015;Sharples, et al, 2016;Roca et al, 2018 ), and (iii) the combination of questionnaire survey and driving simulators (Yang et al, 2005;Wang et al, 2007;Lai, 2010;Cristea and Delhomme, 2014;Zhong et al, 2016).…”
Section: Research Approaches In Designing Vmsmentioning
confidence: 99%
“…Information provision on alternative routes is yet another significant parameter affecting driver diversion behaviour. Findings from different studies are in agreement, and suggest that drivers exhibit higher diversion propensity when such information is transmitted [26][27][28][29]31]. In a much earlier study, though, Benson [32] noted that motorists were not interested in the provision of alternative route information.…”
Section: Introductionmentioning
confidence: 74%
“…Poulopoulou et al [28] and Poulopoulou and Spyropoulou [29], on the other hand, found that incident type does not affect professional driver behaviour. Impact magnitude comprises yet another contributory parameter of driver diversion behaviour, regardless of the driver category explored [25][26][27][28][29][30]. Examples of impact magnitude include road or lane closure, travel times or delay being expressed either qualitatively (e.g.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation